ABOUT THE FESTIVAL “SHARQ TARONALARI” IN SAMARKAND - Shomurotova Mokhichekhra (Melayu Arts and Performance Journal, 2019)
ABSTRACT The international music festival "Sharq taronalari" (Melodies of the East) is one of the major festivals in Central Asia. The main goal and objective of the festival are to popularize the best achievements of the national musical art, to preserve and develop the great traditions of the people, to encourage talents in the field of music and vocal, to further expand international creative relations, to strengthen mutual cultural and spiritual cooperation, and to glorify the ideas of peace, friendship and reciprocal understanding. This forum, held with the assistance of UNESCO, regularly every two years  serves  to  preserve  and  develop the  traditions  of  musical  and  song  art  of  the peoples of the world and to unite Nations and nationalities on the way to noble goals through art. This article says about the festival “Sharq taronalari”, about decision of implementation, on the organization and condition, and also on scientifically – practical conference within the framework of the festival. Keywords: Sharq taronalari, festival, Central Asia, national music art.